2011
DOI: 10.1007/s12678-011-0051-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Evolution Electrocatalysis on AgPd(111) Alloys

Abstract: Recent studies on AuPd(111) alloy surfaces display unexpected hydrogen evolution reaction activities-a unique activity of AuPd alloys with surface fractions of~20% Pd was found. We investigated if this phenomenon also occurs with AgPd alloys. We first deposited Pd on a Ru (0001) substrate. After annealing, cyclic voltammetry investigations showed the same characteristics as Pd (111) single crystals. During Ag deposition, cyclic voltammetry experiments disclose underpotential deposition of Ag on the Pd film jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
3
11
0
Order By: Relevance
“…24 This assumption agrees with the study of free energy diagram of HER in alkaline conditions, which proved that Volmer-Heyrovsky mechanism dominate. 25 However, high Tafel slopes (160-266 mV dec À1 ) obtained here than the theoretical values for Volmer and Heyrovsky processes, have previously been ascribed to high hydrogen adsorption onto the active sites of polycrystalline Pd electrocatalysts, as supplementary reaction step, 26,27 and are also reported in the compared literature (see Table 3).…”
Section: Physical Characterization: Raman Xrd Bet and Tem Measurementssupporting
confidence: 70%
“…24 This assumption agrees with the study of free energy diagram of HER in alkaline conditions, which proved that Volmer-Heyrovsky mechanism dominate. 25 However, high Tafel slopes (160-266 mV dec À1 ) obtained here than the theoretical values for Volmer and Heyrovsky processes, have previously been ascribed to high hydrogen adsorption onto the active sites of polycrystalline Pd electrocatalysts, as supplementary reaction step, 26,27 and are also reported in the compared literature (see Table 3).…”
Section: Physical Characterization: Raman Xrd Bet and Tem Measurementssupporting
confidence: 70%
“…The obtained values suggest that the Volmer step is the rate-determining step (RDS) of the process. Tafel slope value deviations from the theoretical value of 0.120 V dec −1 for the Volmer step as the RDS [34] have been previously reported and explained by the mentioned absorption of hydrogen into the Pd bulk [2,35]. Additionally, it was observed that b values obtained at the three electrocatalysts increased with temperature, which is also reflected in a small decrease of α.…”
Section: Her Studiessupporting
confidence: 55%
“…The higher b c values of the nanocatalysts than the theoretical values ( ca . 120 mV dec −1 ) [49, 50] were attributed to H's surface coverage on polycrystalline Pd nanocatalyst [51]. High b c values were also obtained for compared literature with the nanocatalysts toward the HER, summarized in Table 2.…”
Section: Resultsmentioning
confidence: 80%